Graft‐Infiltrating Macrophages Adopt an M2 Phenotype and Are Inhibited by Purinergic Receptor P2X7 Antagonist in Chronic Rejection. Issue 9 (2nd May 2016) - Wu, C.; Zhao, Y.; Xiao, X.; Fan, Y.; Kloc, M.; Liu, W.; Ghobrial, R. M.; Lan, P.; He, X.; Li, X. C.
Abstract : Macrophages exhibit diverse phenotypes and functions; they are also a major cell type infiltrating chronically rejected allografts. The exact phenotypes and roles of macrophages in chronic graft loss remain poorly defined. In the present study, we used a mouse heart transplant model to examine macrophages in chronic allograft rejection. We found that treatment of C57BL/6 mice with CTLA4 immunoglobulin fusion protein (CTLA4‐Ig) prevented acute rejection of a Balb/c heart allograft but allowed chronic rejection to develop over time, characterized by prominent neointima formation in the graft. There was extensive macrophage infiltration in the chronically rejected allografts, and the graft‐infiltrating macrophages expressed markers associated with M2 cells but not M1 cells. In an in vitro system in which macrophages were polarized into either M1 or M2 cells, we screened phenotypic differences between M1 and M2 cells and identified purinergic receptor P2X7 (P2x7r), an adenosine triphosphate (ATP)–gated ion channel protein that was preferentially expressed by M2 cells. We further showed that blocking the P2x7r using oxidized ATP (oATP) inhibited M2 induction in a dose‐dependent fashion in vitro . Moreover, treatment of C57BL/6 recipients with the P2x7r antagonist oATP, in addition to CTLA4‐Ig treatment, inhibited graft‐infiltrating M2 cells, prevented transplant vasculopathy, and induced long‐term heart allografts survival. These findings highlight the importance of the P2x7r–M2 axis in chronic rejection and establish P2x7r as a potential therapeutic target in suppression of chronic rejection. Abstract : The authors demonstrate an association between chronic heart allograft rejection and preferential enrichment of M2 macrophages in grafts that express the purinergic receptor P2X7, and demonstrate a therapeutic potential for a P2X7 receptor antagonist. See the editorial from Baldwin and Morelli on page 2510 .